Utilization of landfill biogas in the context of sustainable development based on the example of communal landfill in Opole - Mirosława Kaszubska; Małgorzata Wzorek; Krzysztof Koszyk (Economic and Environmental Studies (E&ES), 2017)
This paper presents the results of a study into the application of landfill biogas by applying an example of a biogas power plant situated on-site at the municipal landfill in Opole (MSO). The objective of the study was to analyze the operation of a biogas power plant. During the study, the environmental impact of the facility was assessed. This analysis involved the considerations of a biogas power plant in terms of the social impacts of its operation. An economic assessment was performed, including a comparison of the investment made in this plant with the potential revenues generated from its exploitation. The analysis was performed on the basis of data detailing the amounts of derived biogas and electricity production in the biogas power plant. A number of advantages of the use of the landfill gas are demonstrated along with the impact on the environment in the context of sustainable growth and integration of the social and economic aspects. On the basis of this analysis, we can state clearly that the application of a biogas power plant with the purpose of utilizing the available landfill gas resource forms a technology forms a process that is environmentally-friendly, economically feasible and is characterized by a considerable level of social approval.
Keywords: Q01; Q24; 330; biogas; landfill; biogas power plant